Development Of Medical Infrastructure And Activities Of Hospitals In Uzbekistan During World War II (Eurasian Journal of History, Geography and Economics, 2025)
During the Second World War, the medical infrastructure in the Uzbek SSR developed significantly. The evacuation of millions of people and hundreds of enterprises required a reorganization of the healthcare system. More than one hundred military hospitals were established, serving wounded soldiers and the evacuated population. Both local doctors and evacuated medical workers participated in hospital operations. The number of hospitals and hospital beds increased, while sanitary measures helped to prevent epidemics. The example of Kashkadarya region highlights the role of mobile medical units and front assistance committees